Dietary Patterns and Obesity Risk Among Adolescents in Denpasar City, Bali, Indonesia - Made Pratama Wijaya; Nurul Faidah; Sarah C. Folta (Media of Health Research, 2026)
Adolescent obesity has become a growing public health concern in Indonesia, particularly in urban areas such as Denpasar City, Bali. Rapid urbanization, lifestyle changes, and increased availability of energy-dense foods have significantly altered adolescents’ dietary patterns, contributing to excess weight gain. This study aims to examine dietary patterns and their association with obesity risk among adolescents in Denpasar City through an integrative literature-based analysis supported by empirical contextual evidence. A narrative synthesis method was applied using peer-reviewed national and international studies published between 2021 and 2025, focusing on dietary behaviors, fast food consumption, dietary diversity, and obesity-related outcomes among adolescents. The findings indicate that high consumption of fast food, sugar-sweetened beverages, and low intake of fruits and vegetables are consistently associated with increased obesity risk. Studies conducted in Denpasar and Bali demonstrate similar patterns, reinforced by insufficient physical activity and poor nutritional knowledge. The discussion highlights that modern dietary patterns characterized by high fat and sugar intake significantly elevate obesity risk, while balanced and diverse diets serve as protective factors. In conclusion, unhealthy dietary patterns remain a dominant determinant of adolescent obesity in Denpasar City. Strengthening school-based nutrition education, family involvement, and supportive food environments is essential to mitigate obesity risk among adolescents.